PENGEMBANGAN MEDIA VIDEO PEMBELAJARAN BERBASIS KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS V SDN 2 BABAKTULUNG - Sholikhatun Nikmah; Ifa Seftia Rakhma Widyanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The low level of student understanding of light and its properties at SDN 2 Babaktulung presents a barrier to creative learning, which is still dominated by conventional textbook-based approaches. The primary objective of this research is to develop instructional video media that implements a contextual approach to improve the learning outcomes of fifth-grade students at SDN 2 Babaktulung in science, specifically on the topic of light and its properties. The development stages in this research are guided by the ADDIE model, which consists of five main stages: analysis, design, development, implementation, and evaluation. Data collection in this study involved observation, interviews, pre-tests and post-tests, and questionnaire distribution. This research demonstrates that the resulting instructional video media meets very high validity standards, as indicated by validation scores of 90% from material experts, 84% from media experts, and 86% from language experts and practitioners. In terms of practicality, this media is considered very suitable for use with a readability percentage reaching 96%, student responses of 96%, and teacher responses of 100%. There was a change in the average student score, increasing from 51.25 in the pre-test to 87.5 in the post-test. The N-Gain calculation result of 0.74 indicates a very effective level of media effectiveness. The results of the study indicate that this contextual video media meets the eligibility criteria for use in science learning, as it is considered valid, practical, and effective.